Waktu Mulai, Durasi IMD dan Keberhasilan ASI Eksklusif - Idayati, Idayati; Amin, Erna; Sastrariah, Sastrariah; Wahida, Wahida; Nurdiana, Nurdiana; Cicilia, Fitri (Jurnal Kebidanan Malakbi, 2024)
Early initiation of breastfeeding (EIBF) is crucial for exclusive breastfeeding success and has many benefits for mothers, babies, and families. Moreover, EIBF also contributes to building the quality of the next generation. This study aims to investigate the factors that determine the implementation of EIBF and its effect on exclusive breastfeeding during the postpartum period. The research used an observational analytic approach with a prospective cohort design on all mothers who gave birth in health facilities in the Beru-beru Health Center working area, West Sulawesi Province in 2021. The research sample included mothers who gave birth in the same area, and were willing to participate as respondents and living in the location. The results of the Chi-Square test analysis showed that the start time and duration of EIBF implementation affected exclusive postpartum breastfeeding, with respective p-values of less than 0.001 and 0.001. This research highlights the importance of implementing EIBF by initiating immediate breastfeeding within five minutes after the baby is born and continuing it for at least one hour. Both the start time and duration of EIBF complement each other in achieving successful postpartum exclusive breastfeeding.